The livestock drinking water system as an active reservoir for antimicrobial resistance: A systematic review and one health gap analysis - Sujan Adhikari; Swagat Khanal; Akash Adhikari (PLoS ONE, 2026)
Livestock drinking water distribution systems represent a critical but understudied interface in the epidemiology of antimicrobial resistance. While engineered for production, these systems frequently function as unintended bioreactors where biofilms protect pathogens and facilitate horizontal gene transfer. Following PRISMA and SWiM guidelines, we systematically searched four databases (MEDLINE, Scopus, AGRIS, PubAg) through November 2025 for primary research on antimicrobial resistance in livestock water biofilms. Eligible studies underwent risk-of-bias assessment using JBI tools. Due to substantial methodological heterogeneity in sampling and assays, data were synthesized narratively to characterize resistance prevalence and reservoir dynamics. The synthesis reveals that DWDS biofilms harbor distinct microbial communities compared to transient planktonic or fecal inputs. Critically, these matrices sustain critical priority traits, including multidrug efflux pumps ( adeF ) in swine systems, plasmid-mediated colistin ( mcr-1 to mcr-5 ) and carbapenemase ( blaNDM ) genes. Evidence indicates that standard disinfection protocols often fail to eliminate established biofilms, allowing rapid recolonization by resistant populations within days of treatment. These findings suggest that farm water infrastructure acts as a persistent reservoir for genetic resistance traits, capable of reseeding animal cohorts despite distinct production cycles. We identify a critical surveillance blind spot and conclude that current One Health surveillance strategies should expand beyond bulk water testing to include targeted biofilm sampling. Effective mitigation requires engineering solutions and enzymatic treatments specifically designed to disrupt the protective matrix, thereby closing a significant gap in on-farm biosecurity.